ANALISIS PEMASARAN DAN TRANSMISI HARGA PADA PETANI BOKAR DI DESA LUBUK BATU TINGGAL KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Ari Firma Kumala; Ermi Tetty; Suardi Tarumun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aim is to know and analyze: 1. The channel, margin of rubber marketing and rubber marketing efficiency. 2. The correlation between the price of rubber from factory and the price of rubber in farmer level. 3. The influence of rubber price changing of factory to farmer level at Lubuk Batu Tinggal Village of Lubuk Batu Jaya District of Indragiri Hulu Regency. The research is used of survey method. The sampling method is purposive sampling of 40 farmer that have plantation age between 10-15 years. The second sampling of merchant is using snowball sampling method. The research results shows that in Lubuk Batu Tinggal Village of Lubuk Batu Jaya District of Indragiri Hulu Regency have one rubber marketing chanel. That is farmer to collector merchant to factory. The lowest price in farmer level is Rp.5.500/kg. The highest price level is Rp. 9.200/kg. The lowest price of factory is Rp. 7.050/kg. The highest price level of factory is Rp. 11.480/kg. The average price level of the farmer level on period January 2014 up to Desember 2014 is Rp. 7.084,42. the average price level on factory is Rp. 9.399,17. The margin level of marketing channel between the price in farmer level and factory is Rp. 2.313,08 marketing eficiency is 5,99%. Correlation value between the price in farmer level and factory level is 0,81%. Value of the elasticity of price transmission between the price received from farmers and the price  by factory  0,81%.   Keywords : Marketing, Margins, Price Transmission, Elasticity.